Анализ факторов активизации когнитивных процессов у обучающихся; Artium Magister; Т. 23, № 1 - Лизунков В. Г. Владислав Геннадьевич; Трофимов А. В. Александр Валерьевич; Новиков А. О. Антон Олегович; Новиков Е. О. Егор Олегович (2023, 2023)
Заглавие с экрана